If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(9t+10)=56
We move all terms to the left:
2(9t+10)-(56)=0
We multiply parentheses
18t+20-56=0
We add all the numbers together, and all the variables
18t-36=0
We move all terms containing t to the left, all other terms to the right
18t=36
t=36/18
t=2
| 7+p=241 | | 90=81-2x-51 | | y=-81(91)+33+ | | 7.75/5=n | | 3y-3+7y=2y+13 | | g-986=-435 | | 0.9k-15.41=-15.41+16.8k+11.1k | | 120+7m=239 | | 3/5x-7=1/4x+8 | | 5x+7=3x+3=90 | | 3x-8=8x-13 | | z+24=999 | | 5h=2h2 | | -2y+8=20-2y-12 | | y/15=19 | | 3/4(4x-16)=1/3(6x+18) | | c-250=150 | | 4x^2+16x+9=-3 | | y=25.4(-7)= | | 11x-5.5x+12=144/24+3x | | x+x+x-30-10+70=180 | | 3(2w-1)=7w+9-3w | | 379.74=200x=0.68 | | 4x-2x+6x=10x-2x | | X-2x÷5=36 | | 24n-135=225 | | u+6=-4 | | n=30=20 | | ½e=¼ | | 2.6c=0.95+2.7c | | 4(t+3)=35 | | x-10=41* |